2012
DOI: 10.5539/ibr.v5n7p73
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cooperatives and CSR: The Case of the French Agricultural Sector

Abstract: Changes in French environmental legislation since 2010 require major companies to establish a corporate social responsibility policy. Although very small, small, and medium-sized companies are not as yet required to comply with these obligations, some of them consider that it is necessary to develop provisions addressing this concept, and even to fully embrace them. In view of the particular character of VSEs and SMEs, which are informal in nature, characterized by intuitive strategies, and have limited access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Just as an increase in innovation can foster competitiveness, it allows for an increase in the effect on CSR . Previous studies have already demonstrated a connection between the capacity for innovation and commitment to CSR (Taddei & Delécolle, 2012). Graafland and Zhang (2014) highlight that the literature has paid more attention in recent years to the association between innovation and CSR.…”
Section: Justification Of the Hypothesesmentioning
confidence: 98%
See 2 more Smart Citations
“…Just as an increase in innovation can foster competitiveness, it allows for an increase in the effect on CSR . Previous studies have already demonstrated a connection between the capacity for innovation and commitment to CSR (Taddei & Delécolle, 2012). Graafland and Zhang (2014) highlight that the literature has paid more attention in recent years to the association between innovation and CSR.…”
Section: Justification Of the Hypothesesmentioning
confidence: 98%
“…This is reflected in the opinions of the European Commission (2002), which defines CSR as a company's contribution to sustainable development, in addition to covering agreements and legal commitments and duties of the company with its stakeholders (stakeholders), where it adopts a medium and long-term view of the business. It is necessary for a company to be socially responsible not only to fulfill its obligations, but also to go beyond them and make greater investments in human capital, in the environment, and in the relationships with its stakeholders (Taddei & Delécolle, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the existing spectrum of definitions, the concept of alternative entrepreneurship is, in many ways, pioneering the development and practice of CSR, using approaches that are more intuitive than formalized. Unfortunately, these kinds of entrepreneurial activities lack the resources and information compatible with a CSR certification process and its management (Taddei and Delecolle 2012).…”
Section: Alternative Entrepreneurship and Csrmentioning
confidence: 99%
“…In order to account for sample-size errors and non-response errors the sample was doubled and rounded up to 800 (Hair et al, 2008). The managers and owners were seen as the most appropriate respondents because they are the key decision makers (Cochet and Chi Vo, 2012;Taddei and Dele'colle, 2012). The process of data collection took about five months in 2013 and involved research assistants.…”
Section: Population and Samplementioning
confidence: 99%